(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Abstract. Introduction. The constant development of technologies, changing forms of threats and the need to adapt to new conditions will require organizations to constantly improve their security systems. The purpose of this work is to systematize theoretical provisions and substantiate practical recommendations regarding the organization of protection of digital financial accounting data. Methods. In the process of research, the method of induction was used at the stage of collecting, processing and systematization of the received information, the method of analysis and synthesis - to combine the constituent elements of economic phenomena in a single process. Results. The essential characteristics of the concepts of information security, digital security and data cyber security in the context of economic security of the enterprise are revealed. A set of measures in the system of organizing digital security of financial accounting data has been identified. National and international legal acts, standards and recommendations define mandatory requirements for data storage, processing and transmission, thus providing a legal basis for the implementation of information security policies. The main directions of state policy in the field of information security have been determined. The state in which business entities currently work is accompanied by constant cyber-attacks both on the enterprises themselves and on the totality of their digital data in the field of accounting and taxation. The main measures to ensure cyber security for critical infrastructure enterprises have been determined. They singled out the main problems of digital information protection in accounting, namely: data leakage; software attacks; phishing and social engineering; malware. The main methods of preventing cyber threats are summarized. Recommendations on the organization of the system for ensuring the security of digital data in financial accounting have been formed. The actions of the accounting staff of the enterprise or the enterprise of the partner, which may create a threat of information leakage, are singled out. A set of information sources in need of protection has been identified. Conclusions. The digital information protection system should become an element of the company’s accounting policy, and its implementation will contribute to the economic security of the business entity.